2019
DOI: 10.3102/1076998619838226
|View full text |Cite
|
Sign up to set email alerts
|

Kernel Equating Using Propensity Scores for Nonequivalent Groups

Abstract: When equating two test forms, the equated scores will be biased if the test groups differ in ability. To adjust for the ability imbalance between nonequivalent groups, a set of common items is often used. When no common items are available, it has been suggested to use covariates correlated with the test scores instead. In this article, we reduce the covariates to a propensity score and equate the test forms with respect to this score. The propensity score is incorporated within the kernel equating framework u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…In the absence of anchor tests, then, collateral information has been used for test score linking either as surrogate anchors (Wallin & Wiberg, 2019) or to weight samples to approximate equivalent groups (Haberman, 2015; Livingston, 2014; Longford, 2015). These methods appear to work well when collateral information is not only abundant but also strongly statistically related to the test scores.…”
mentioning
confidence: 99%
“…In the absence of anchor tests, then, collateral information has been used for test score linking either as surrogate anchors (Wallin & Wiberg, 2019) or to weight samples to approximate equivalent groups (Haberman, 2015; Livingston, 2014; Longford, 2015). These methods appear to work well when collateral information is not only abundant but also strongly statistically related to the test scores.…”
mentioning
confidence: 99%
“…According to Wallin and Wiberg (2019), equating non-equivalent test groups requires adjusting for two sources of bias: differences in the difficulty of the forms and differences in the abilities of the test groups. A proper equating conversion should address both of these, but when the second is observed, some substitutes are required in place of ability.…”
Section: Data Set and The Test Equating Designmentioning
confidence: 99%
“…In the second step, the estimated score probabilities were generated by mapping the presmoothed score distributions into the score probability vectors for X and Y using a design function. This function, known as the design function, depends on the data collection design (see Wallin and Wiberg (2019) for the explicit expression of the design function for the NEC design).…”
Section: Estimation Of the Score Probabilitiesmentioning
confidence: 99%
“…Using operational data, Haberman concluded that equating with pseudoequivalent groups yielded results not identical with but similar to the operational results. Under the framework of kernel equating, Wallin & Wiberg (2019) examined the use of propensity scores for equating with nonequivalent groups when common items were unavailable and found the results satisfactory.…”
Section: No Samplementioning
confidence: 99%